Demographic Variations in Patient Populations and Regional Distributions Between Male and Female Ophthalmologists in the United States: Cross-Sectional Analysis. (17th November 2021) - Kalavar, Meghana; Watane, Arjun; Cavuoto, Kara M; Vanner, Elizabeth a; Sridhar, Jayanth
ABSTRACT: Purpose : To determine if patient demographics differ by ophthalmologist gender. Methods : Demographic data on U.S. ophthalmologists were collected from the 2017 Medicare Physician and Other Supplier National Provider Identifier Aggregate Report. Results : Of the 17, 230 ophthalmologists included, female ophthalmologists (23.7%) provided care for a smaller proportion of White patients (77.4% ± 24.9% female, 81.0% ± 22.1% male; p < .001), had younger beneficiaries (73.8 ± 3.2 years old females, 74.8 ± 2.9 years old males; p < .001) and had a higher proportion of female beneficiaries per provider (61.1% ± 4.6% females, 59.6% ± 4.0% males; p < .001). Average age of beneficiaries and number of beneficiaries were correlated with years since medical school (rho = 0.283, rho = 0.148; both p < .001). The number of Medicare beneficiaries, proportion of female beneficiaries, years since medical school and group practice size were independently associated with physician gender ( p < .001). Conclusion : Female ophthalmologists saw a larger proportion of ethnically diverse, younger, female patients.